Forums Assignment Help Solve the equation

Viewing 2 posts - 1 through 2 (of 2 total)
  • Author
    Posts
  • #1930
    ahprofessional
    Participant

    Solve the equation

    5(-3x – 2) – (x – 3) = -4(4x + 5) + 13

    #10515
    john Smith
    Participant

    5(-3x – 2) – (x – 3) = -4(4x + 5) + 13

    -15x – 10 – x + 3 = -16x – 20 +13

    -16x – 7 = -16x – 7

    0 = 0

    The statement is true for all values of x and therefore all real numbers are solutions to the given equation.

Viewing 2 posts - 1 through 2 (of 2 total)
  • You must be logged in to reply to this topic.